The Contribution of Agricultural Sector Oneconomic Districs/Cities in North Sumatra Province - Muhammad Buhari Sibuea (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2017)
The agricultural sector is one of the most potential sectors to the growth and development of national economy, both in terms of income and employment.